IDENTITIES OF THE SUPREME PATRIARCH OF RATTANAKOSIN - Suthanaphinyo, Suphakkhathat (Journal of MCU Nakhondhat, 2023)
This article aimed to study identities of the Supreme Patriarch relying on data from the book entitled “The Biography of 19 Supreme Patriarchs of Rattanakosin” of Wat Bowonniwet Vihara publicized to celebrate the 96th birthday anniversary of His Holiness Somdet Phra Nyanasamvara, the Supreme Patriarch of Thailand on October 3, 2009, and using the identity concept as an analytical framework.The result revealed that the Supreme Patriarch of Rattanakosin had 4 outstanding social identities: 1) being a teacher, 2) being a philosopher, 3) being an educator, and 4) being a governor. These identities were relevant and overlapped each other more than one identity, and each had its dynamic that could be able to be adjusted according to the social context in each era. However, all of them obviously played a key role in honoring each Supreme Patriarch of Rattanakosin. In addition, it was found that Supreme Patriarch was a social group playing an important role in maintaining nation, religion, and monarchy institutions, being a spiritual anchor for people of all classes in Thai society, sustaining society and creating various contributions to Thai society continuously for a long time. Therefore, social identity of 19 Supreme Patriarchs of Rattanakosin is being venerable persons of Thai society. It can be said that the identity of the Supreme Patriarchs of Rattanakosin is “being the symbol of goodness.”